OP71 Comparing coronary mortality reductions by shifting the population blood pressure distribution versus improved management of hypertensive patients: modelling study. (2nd September 2014) - Guzman Castillo, M; O'Flaherty, M; Couch, P; Sperrin, M; Lloyd, S; Soiland-Reyes, C; Green, B; Kypridemos, C; Gillespie, DOS; Allen, A; Buchan, I; Capewell, S
Abstract : Background: Blood pressure reduction is an important target for the prevention of coronary heart disease (CHD). In 1982, Rose proposed that small population-wide reductions in blood pressure, through public health measures to reduce salt intake, might deliver larger reductions in CHD mortality than by treating hypertensive patients. We aimed to estimate the potential for each strategy to reduce future CHD deaths in England and Wales. Methods: We used the Stock of Health (SoH) model, where each individual is born with a 100% stock which then depreciates year-by-year, reflecting fixed and modifiable risk factors. A CHD death occurs when the individual's CHD's SoH falls below a critical point. Births, deaths and risk factor distributions were obtained from the Office of National Statistics and the Health Survey for England. Model parameters were calibrated using data from the US Cardiovascular Lifetime Risk Pooling Project. We modelled ten policy scenarios: population-wide, individual-based and combination strategies. The population-wide strategies were: a systolic blood pressure (SBP) reduction of 0.1 mmHg achieved by health promotion media strategies (Pop1), a 1.3 mmHg reduction achieved by mandatory salt reformulation (Pop2) and an attainable goal where SBP levels fall to those observed in the US population (Pop3). The individual-based strategies assumed that in currently uncontrolled hypertensive patients, control was then achieved in 30% (Indi1) and 50% (Indi2) of them. Results: We forecast that approximately 467, 200 CHD (95% CI 466, 900–467, 600) deaths may occur between 2013 and 2030. By controlling 30% and 50% of hypertensive patients, we predict approximately 3800 (3200–4300) and 6200 (5700–6800) fewer deaths respectively. Conversely, we predict approximately 1300 (800–1900) fewer deaths by health promotion; some 16, 400 (15, 800–16, 900) fewer deaths by mandatory reformulation and approximately 25, 400 (24, 900–25, 900) fewer deaths by gradual SBP declines to US levels. Combining Pop1 and Indi1 might achieve approximately 5100 (4500–5600) fewer deaths in 2030; whereas combining Pop1 and Indi2 could achieve some 7500 (2000–13, 000) fewer deaths. Combining Pop2 and Indi1 might prevent approximately 19, 700 (19, 200–20, 300) deaths; while combining Pop2 and Indi2 could prevent or postpone some 21, 900 (21, 400–22, 400) deaths by 2030. Conclusion: Both population-wide salt reduction policies and individual-based treatment strategies could substantially reduce CHD deaths in England and Wales. Even greater reductions in mortality might be achieved by reducing SBP to US levels. However, there is no clear single successful intervention, but both types of strategies are needed to maximise our chances of controlling the burden of mortality attributable to blood pressure.